2011
DOI: 10.1638/2010-0158.1
|View full text |Cite
|
Sign up to set email alerts
|

Immunocontraception in Eastern Gray Squirrels (Sciurus carolinensis): Morphologic Changes in Reproductive Organs

Abstract: Eastern gray squirrels (EGS) (Sciurus carolinensis) damage trees through bark stripping or gnawing due to territorial marking or agonistic gnawing behavior in concert with higher densities. This study was conducted to determine the effects of a contraceptive vaccine on EGS and its reproductive organ histology. Free-ranging urban EGS were vaccinated with the immunocontraceptive GonaCon. All EGS were > or = 6 mo of age as determined by a combination of pelage characteristics and body weights. The vaccine was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The GonaCon treatments resulted in reduced scrotal size in UCD fox squirrels, similar to the reduced testis size documented in white-tailed deer (Killian et al 2005, Curtis et al 2008, Gionfriddo et al 2011b), feral pigs (Killian et al 2006), domestic cats (Levy et al 2004), and eastern gray squirrels (Pai et al 2011). Pai et al (2011) documented testicular, prostatic, and epididymal atrophy in GonaContreated eastern gray squirrels, as well as atrophy of tubuli and prostatic glandular lumen. We believe that the fox squirrels in our study exhibited similar atrophy in these structures, but we did not test this directly.…”
Section: Response Variable and Random Effectssupporting
confidence: 70%
“…The GonaCon treatments resulted in reduced scrotal size in UCD fox squirrels, similar to the reduced testis size documented in white-tailed deer (Killian et al 2005, Curtis et al 2008, Gionfriddo et al 2011b), feral pigs (Killian et al 2006), domestic cats (Levy et al 2004), and eastern gray squirrels (Pai et al 2011). Pai et al (2011) documented testicular, prostatic, and epididymal atrophy in GonaContreated eastern gray squirrels, as well as atrophy of tubuli and prostatic glandular lumen. We believe that the fox squirrels in our study exhibited similar atrophy in these structures, but we did not test this directly.…”
Section: Response Variable and Random Effectssupporting
confidence: 70%
“…Available data on their potential impact on the population dynamics of other squirrel species [54] suggest they could reduce populations, without eradicating them, if at least 70% of the females were treated [54][55][56][57]. At present, this requires the capture of the animals in order to inject the vaccine, and it could be necessary to capture and treat each animal more than once, since the long-term effects of the vaccine have not been demonstrated so far [58,59]. On the basis of a theoretical model, [56] concluded that 90% of females should be treated in order to eradicate a grey squirrel population within 7/8 years, ensuring a constant sterilization effort.…”
Section: Equilibriummentioning
confidence: 99%
“…However, it soon became apparent that a GnRH-based contraceptive could apply to other species as well. Because GnRH is common to all mammals, the GonaCon immunocontraceptive vaccine has induced contraception in many overabundant mammalian species, including white-tailed deer, 47 elk (Cervus elaphus), 22 wild horses, 24,25,18 bison, 50 California ground squirrels (Spermophilus beecheyi), 53 prairie dogs, 66 , gray squirrels (Sciurus carolinensis), 54,65 captive Norway rats (Rattus norvegicus), 44 domestic and feral swine and wild boar, 26,27,51,37 brushtail possums (Trichosurus vulpecula), 8 and tammar wallabies (Macropus eugenii). 59 In the United States, all of these uses in wildlife will be regulated by the Environmental Protection Agency.…”
Section: Use Of Gonacon For Reproductive Behavior and Disease Managmentioning
confidence: 99%